Best served cold - Wagner, David P. (Wagner, David P. Rick Montoya Italian mysteries, 2023)
"When an old college friend leading a religious tour in Assisi asks interpreter Rick Montoya to fill in for their guide who's gone missing, Rick is happy to oblige. He's looking forward to seeing his old friend, and the food and wine of Umbria sound like the perfect reward for a tense translation job he's just completed for the police in Palermo involving witness testimony against the mafia. But when the shady tour guide is found dead the next morning under suspicious circumstances, Rick's relaxing gig turns into an unofficial job assisting the local police inspector with her interviews of the tour group members. Could one of the pious pilgrims be a cold-blooded killer? Or has one of the victim's many shady dealings finally caught up with him?"--